2008
DOI: 10.1007/s11999-008-0312-6
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective: Engineering Periosteum for Structural Bone Graft Healing

Abstract: Autograft is superior to both allograft and synthetic bone graft in repair of large structural bone defect largely due to the presence of multipotent mesenchymal stem cells in periosteum. Recent studies have provided further evidence that activation, expansion and differentiation of the donor periosteal progenitor cells are essential for the initiation of osteogenesis and angiogenesis of donor bone graft healing. The formation of donor cell-derived periosteal callus enables efficient host-dependent graft repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
172
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(179 citation statements)
references
References 101 publications
2
172
0
5
Order By: Relevance
“…Periosteal cell populations modify their potential with age, with a significant increase in IL-6 mRNA expression and receptor activator of nuclear factor kappa-B ligand/osteoprotegerin ratio [6]. In vivo studies indicated that PDPCs are indispensable for bone graft healing and remodeling [7].…”
Section: Introductionmentioning
confidence: 99%
“…Periosteal cell populations modify their potential with age, with a significant increase in IL-6 mRNA expression and receptor activator of nuclear factor kappa-B ligand/osteoprotegerin ratio [6]. In vivo studies indicated that PDPCs are indispensable for bone graft healing and remodeling [7].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to further enhance bone regeneration therapies, and taking advantage of the benefits of the periosteum, the use of periosteal grafts has emerged as an attractive strategy [7]. An ideal periosteal graft would not only provide a physical structure that facilitates osteoconduction, but also osteoinductive signals that stimulate osteogenesis and ultimately promote biomineralization [8].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of osteocytes during allograft devitalization may contribute to an overall decrease in graft resorption and remodeling as compared with autograft controls [45]. Osteocytes, however, have no contribution to early osteogenesis of bone grafts [47], so we believe our approach will still enhance allograft integration and healing, even in the absence of these cells. Furthermore, by altering PEG degradation kinetics or hydrogel MSC densities we believe we can exercise temporal control over the initiation of remodeling and thereby increase early matrix production and ossification [45,48].…”
Section: Limitationsmentioning
confidence: 94%
“…Allografts remain the gold standard for treating critical-sized bone defects but have slow bone formation and minimal engraftment, resulting in fibrotic nonunions and brittle fractures [44,45,47,48]. In contrast, autografts completely heal, mediated by the periosteum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation